PENGARUH DIAMETER KAWAT ELEKTROMAGNET PADA SALURAN BAHAN BAKARDAN PEMASANGAN 9POWER PADA KABEL BUSI TERHADAP TORSI DAN DAYA PADA SEPEDA MOTOR YAMAHA JUPITER Z TAHUN 2007 - Salatin, Sirrus Sandy (Jurnal Nosel, 2014)
The objective of this research were to investigate: (1) the effect of the diameter of electromagnetic coil wire in the fuel line on the torque and power of Yamaha Jupiter Z motorcycle in 2007; (2) the effect of the position of installation and number of 9power of the spark plug wire on the torque and power of Yamaha Jupiter Z motorcycle in 2007; and (3) the simultaneous effect of the diameter of electromagnetic coil wire and the position of installation of 9power into the spark plug wire on the torque and power of Yamaha Jupiter Z motorcycle in 2007. This research used the experiment method. The research was conducted in Mototech (Motorcourse Technology) with the address on South Ring Road, Kemasan, Singosaren, Banguntapan, Bantul, Yogyakarta. The instrument used to measure the torque and power was the dynotest of Dynojet SD325 type. The population of this research was Yamaha Jupiter Z in 2007 motorcycle and the sample of this research was Yamaha Jupiter Z in 2007 with machine number 2P2675042. The data of this reseach were analyzed by using the Two-way Analysis of Variance (ANNOVA). The results of this research were as follows: (1) there was a significant effect of the diameter of electromagnetic coil wire on the torque and power of Yamaha Jupiter Z motorcycle as indicated by the value of maximal torque of 8.82 Nm and the value of maximal power of 6263.88 Nm/s with the diameter of electromagnetic coil wire of 0.20 mm; (2) there was not any effect of the position of installation and number of 9Power of the spark plug wire on the torque. However, there is a significant effect of the position of installation and number of 9Power of the spark plug wire on the power of Yamaha Jupiter Z motorcycle as pointed out by the value of maximal power of 6263.88 Nm/s with all types of treatment of position of installation and number of 9Power; and (3) there was not any simultaneous effect of the diameter of electromagnetic coil wire and the position of installation and number of 9Power of the spark plug wire on the torque. However, there was a significant simultaneous effect of the diameter of electromagnetic coil wire and the position of installation and number of 9Power of the spark plug wire on the power as signified by the value of maximal power of 6263.88 Nm/s with the diameter of electromagnetic coil wire of 0.20 mm and the position of 1 piece of 9Power near the spark plug wire.